Design of bandwidth-efficient unequal error protection LDPC codes - Sandberg, Sara; Von Deetzen, Neele (IEEE transactions on communications, 2010)
This paper presents a strategy for the design of bandwidth-efficient LDPC codes with unequal error protection. Bandwidth efficiency is obtained by appropriately designing the codes for higher order constellations, assuming an AWGN channel. The irregularities of the LDPC code are designed, using the Gaussian approximation of the density evolution, to enhance the unequal error protection property of the code as well as account for the different bit error probabilities given by the higher order constellation. The proposed code design algorithm is flexible in terms of the number and proportions of protection classes. It also allows arbitrary modulation schemes. Our method combines the design of unequal error protection LDPC codes for the binary input AWGN channel with the code design for higher order constellations by dividing the variable node degree distribution into sub-degree distributions for each protection class and each level of protection from the modulation. The results show that appropriate code design for higher order constellations reduces the overall bit-error rate significantly. Furthermore, the unequal error protection capability of the code is increased, especially for high SNR.